Mingled Measures: Gothic Parody in Tales of Wonder and Tales of Terror - Thomson, Douglass (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractLabeled by Louis Peck a “bibliographical hazard,” Tales ofTerror has long suffered from two misrepresentations: 1) it has been frequently attributed to M.G. Lewis, although no external evidence exists to support the claim; and, somewhat paradoxically, 2) it has been dismissed as a mere burlesque of Lewis’s Tales of Wonder, despite the fact that the majority of its poems treat Gothic themes in a serious manner. The parodic spirit pervading Tales of Wonder stems in part from Lewis’s attempt toanticipate and defuse critical alarm about his Gothic works. The writers of Tales of Terrorcarry on this double-edged treatment of the Gothic, especially in the volume’s“Introductory Dialogue” between a defender and opponent of Gothic poetry. Thedestabilizing presence of a satiric voice in ballads specifically selected for their recoveryof a more forceful, authentic, and native idiom of poetry also raises an interestingsecondary question: whether Gothic ballads can be free of the ironic consciousness theywere originally and ostensibly designed to exclude.